Optimal design of a structured fixed-bed reactor using geometry optimization and Stratoconception printing process. (October 2021) - Courtais, Alexis; Lesage, François; Privat, Yannick; Pelaingre, Cyril; Latifi, Abderrazak M.
Highlights: Development of a constrained shape optimization approach based on the adjoint system method. Determination of the optimal shape of the packing which maximizes the conversion rate in fixed-bed reactors. Treatment of manufacturability constraints using the Voronoi diagram and a projection method. Manufacturing of the optimal shapes using a Stratoconception 3D printing technique. Abstract: The aim of this paper is to determine the shape of a fixed-bed reactor which maximizes the conversion rate under the constraints of process model equations (i.e. continuity, Navier–Stokes, and mass balance equations), energy dissipation, iso-volume, and manufacturing. Incompressible fluid, laminar flow regime and steady-state conditions in the reactor are the main assumptions taken into account. The optimization method developed is based on the adjoint system method and OpenFOAM framework is used as CFD solver to compute the state vector and its adjoint variables introduced by the optimization approach. The algorithm developed is then tested on two different cases, a reactor where a first order homogeneous reaction takes place and another one involving a surface reaction. The optimization results show a significant improvement of the conversion rate by 2.7% in the first case, and by 16% in the second one. Finally, initial and optimal shapes are manufactured using a 3D printing technique.